On Gas Seepage Regularity in Different Structural Bituminous Coal and Its Influence on Outburst-Coal Breaking - Jie Zheng; Linfan Chen; Gun Huang; Jun Wang; Weile Geng (Applied Sciences, 2025)
Coal and gas outburst remains a critical and persistent challenge in coal extraction, posing a profound threat for mine safety. The underlying mechanisms of such disaster, particularly the gas-driven coal fragmentation, continue to elude comprehensive understanding. To explore this problem, in this paper, gas seepage regularity in different structural bituminous coal and its influence on outburst-coal breaking were investigated through strength tests, isothermal adsorption tests, and gas seepage tests of stressed coal under various conditions. The results indicated that coal permeability decreased as axial stress, confining pressure, and gas kinetic diameter increased. That meant outburst-induced abrupt stress unloading and coal matrix destabilization changed gas seepage characteristics. As a result, a self-reinforcing cycle effect where outburst-coal breaking and gas seepage are mutually stimulated was formed in a short time period when outbursts initiated, which further promoted outburst-coal breaking and outburst initiation. The findings of this study enhance our understanding of the mechanism of gas participating in coal fragmentation during outbursts, which are significantly conducive to gas disaster prevention, sustainable coal production, and efficient CBM development, further ensuring global energy security.